Strategi Peningkatan Nilai Religi Warga Desa Bonto Marannu Kecamatan Moncongloe Kabupaten Maros - Kurnaemi Anita; Muhammad Nirwan Idris (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2023)
The purpose of this study is to reveal several strategies carried out by Makassar STIBA KKN students to increase the religious value of the residents of Bonto Marannu Village, Moncongloe District, Maros Regency, South Sulawesi. The method of implementing the KKN program begins with field observations of the conditions of the local community as an initial approach using SOAR analysis adapted to the moment of the month of Ramadan which then produces several religious programs including: (1) TKQ-TPQ Learning and Tahfiz Weekend; (2) Al-Qur’an Learning Dirosa Method; (3) Taklim Muslimah and Muslimah Grand Recitation; (5) Funeral Management Training; (6) Tabligh Akbar and Iftar Together. All of these programs went well with the enthusiastic support of the local community and succeeded in bringing about the expected changes. So that the results of the KKN work appear to be measurable from changes in attitudes and behavior of people who are more religious, in the form of enthusiasm for attending taklim and science assemblies, building muamalah and better communication with fellow citizens, as well as the ongoing commitment to continue to participate in the program that will be handled by Muslimah Wahdah Maros.